2018
DOI: 10.1016/j.biortech.2017.11.094
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of astaxanthin and fatty acid pathways in Haematococcus pluvialis in response to different LED lighting conditions

Abstract: Haematococcus pluvialis is a green microalga of major interest to industry based on its ability to produce large amounts of astaxanthin. Biosynthesis of astaxanthin and its mono- and di-esters was significantly stimulated under 150 μmol m s of white LED (W-150) compared with lower light intensities, but the highest astaxanthin amounts were produced under 70 μmol m s of blue LED (B-70). Transcripts of astaxanthin biosynthesis genes psy, crtO, and bkt2 were upregulated under W-150, while psy, lcy, crtO, and crtR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 43 publications
(46 reference statements)
10
75
0
1
Order By: Relevance
“…No difference was found across days in control samples, suggesting that the modification of carotenoid profile was due to the action of IAA and not culture conditions. These results are in agreement with a previous study of (Ma et al 2017). Our data also showed that LCYb and LCYe both increased in expression, although the induction was more pronounced in LCYb.…”
Section: Iaa-induced Carotenoid Profiles and Associated Gene Expressionsupporting
confidence: 94%
“…No difference was found across days in control samples, suggesting that the modification of carotenoid profile was due to the action of IAA and not culture conditions. These results are in agreement with a previous study of (Ma et al 2017). Our data also showed that LCYb and LCYe both increased in expression, although the induction was more pronounced in LCYb.…”
Section: Iaa-induced Carotenoid Profiles and Associated Gene Expressionsupporting
confidence: 94%
“…Haemaococcus lacustris is not only able to produce a substantial amount of TAG but also the highest content of AST under stress conditions, which represents a leading algal candidate of industrial potential [29][30][31][32][33][34][35]. For example, HL and ND stresses can effectively promote the accumulation of AST and TAG in H. lacustris [32][33][34][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…AST/TAG accumulation and HpDGAT2 genes transcription expression upon HL and ND stresses High light (HL) and nitrogen de cient (ND) stresses can effectively promote the accumulation of AST and TAG in H. lacustris [32][33][34][50][51][52][53]. To understand the relationship between HpDGAT2s expression and TAG/AST biosynthesis, time-course patterns of algal biomass, transcription expression, total AST (T-AST), and total TAG (T-TAG) contents in photoautotrophic cultures of H. lacustris under HL, ND, and double HL+ND stresses were studied ( Fig.…”
Section: Molecular Cloning and Bioinformatics Analysis Of Hpdgat2s Genesmentioning
confidence: 99%
See 2 more Smart Citations